Cenários de risco à desertificação no semiárido sergipano - Gois, Douglas Vieira (2020)
The arid and semi-arid regions of the globe have geoecological peculiarities, especially the rainfall variability, which hinder the development of agriculture. Such condition, combined with the historical situation of overexploitation of natural resources, linked to predatory activities carried out on the fragile geoenvironmental framework of this space, gives rise to the process of great environmental degradation, called desertification. The desertification process consists of land degradation in arid, semi-arid and dry sub-humid areas, resulting from several factors, including climatic variations and anthropogenic derivations, resulting in negative impacts both for the environmental domains and for the population affected by it. According to the Programa de Ação Estadual de Combate a Desertificação (PAE-SERGIPE), in the state of Sergipe a northwestern area of the state has a high risk of desertification, and a southwestern portion that presents a moderate risk of triggering the process. However, this finding is based on large scale studies, anchoring themselves, especially on secondary data that do not connote the particularities of the study area, thus resulting in generalized results. In this sense, the present research aimed to analyze the desertification risk scenarios in the Sergipanos municipalities of Canindé de São Francisco and Poço Verde, in the period of 2018 and 2050 (present and future), evaluating the main vectors of degradation and the correlations with anthropogenic derivations in the configuration of scenarios of advancing of degraded / desertified areas. To achieve this goal, multiple methodological procedures were used, namely: literature review; documentary research; elaboration and analysis of cartographic documents, based on remote sensing and geoprocessing techniques, focusing on geostatistical modeling; in addition to field work for on-site analysis of the proposed desertification indicators. In the current scenario, it can be highlighted that in the municipality of Canindé de São Francisco there is a preponderance of environments with high risk (high and very high), where 47,6% of the territory falls into this class, while Poço Verde, located in an area of higher rainfall coefficients and less climatic variability, it has 29,5 % of the territory with high risk (high and very high) to desertification.However, projecting for the future scenario, taking into account the anthropogenic derivations, especially mechanized agriculture (grain production), and extensive livestock activities, both municipalities present an increased risk of desertification. In the future scenario, Canindé de São Francisco presented a percentage increase of 36.7% in high risk areas, what corresponds to 64,9% of its territory. The municipality of Poço Verde, with the increase in climatic severity, presents an increase of 129%in relation to the current scenario, which corresponds to 67.5% of the municipality's territorial area.Therefore, the intensification of monoculture systems with the greatest potential for impact on soil associated with climate change might represent an increase in this process of environmental degradation and therefore on desertification risk.________________________________________________________________________________________________________________________________